1979
DOI: 10.1002/kin.550110302
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of n‐butyraldehyde photolysis in the vapor phase at 313 nm

Abstract: The photolysis was investigated at 313 nm wavelength,253-529 K temperatures, and 4 X 10-"-2 X mol.photon/cm%ec light intensities by determining the quantum yields of 20 reaction products. Primary quantum yields for the seven primary processes and rate constant ratios, rate constants, and Arrhenius parameters for secondary processes were derived on the basis of the suggested reaction scheme. The dependence of the quantum yields of the four major primary processes on experimental conditions was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
1
8
2
Order By: Relevance
“…is at all significant under our conditions [l]. We determined k8/k51'2 = 2.53 x lo-' mol-'" cc112 s-'12 at 22°C which agrees reasonably with the value of 9.54 x mol-l12 ccl" s-'" given by Kerr and Calvert at 24.5" [7]. The comparable rate constant ratios in the photolysis of azoethane show a similar spread [l].…”
Section: Resultssupporting
confidence: 85%
“…is at all significant under our conditions [l]. We determined k8/k51'2 = 2.53 x lo-' mol-'" cc112 s-'12 at 22°C which agrees reasonably with the value of 9.54 x mol-l12 ccl" s-'" given by Kerr and Calvert at 24.5" [7]. The comparable rate constant ratios in the photolysis of azoethane show a similar spread [l].…”
Section: Resultssupporting
confidence: 85%
“…If cyclobutanol were present, these daughter ions would contribute to our m / z = 44 signal and affect the VA cross-section determination. Tadić et al did not observe cyclobutanol as a product in the photolysis of n -butanal, 3-methylbutanal, or 3,3-dimethylbutanal and give an upper limit for cyclobutanol formation from n -butanal of 10%. , Förgeteg et al report some formation of cyclobutanol from n -butanal photolysis and give a quantum yield for cyclobutanol formation that is ∼16% of the quantum yield for VA formation . We do not see any evidence of cyclobutanol (AIE = 9.56 ± 0.02) formation in our experiment .…”
Section: Resultscontrasting
confidence: 49%
“…Early studies on the photolysis of butanal reported AC and ethene as the Norrish type II products. , Tadić et al used time-resolved infrared absorption spectroscopy to show that this is incorrect and that AC is only a secondary product formed from the tautomerization of VA produced in the Norrish type II reaction. Our data support this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Photodissociation of aldehydes produces free radicals, which are subsequently involved in other atmospheric reactions and reaction cycles. There have been a number of studies devoted to the photodissociation of the simplest alkyl aldehydes, such as HCHO, CH 3 CHO, C 2 H 5 CHO [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], but a relatively small number devoted to longer chain aldehydes, such as C 3 H 7 CHO, C 4 H 9 CHO [ 17 , 18 ] and iso -pentanal and tert -pentanal [ 32 ].…”
Section: Introductionmentioning
confidence: 99%